Revision approach to shaping notion to the theory Interior Troops official-combat activity - Lavnichenko, О. V.; Hodlevskyi, S. О.; Hunbin, К. Yu. (Honor and Law, 2019)
In the articles resulted where what approaches in relation to clarification of concepts of kind, form and method, official-battle actions by internal troops at implementation of the fixed tasks due to introduction of certain distinctive signs of actions of troops.